A Analysis Study of Diagnostic Quality and Accuracy of Post Mortem Magnetic Resonance Imaging as An Alternative to Autopsy in The Diagnosis of Death : A Comprehensive Systematic Review - Assyifa Amalia Amin; Prijo Sidipratomo (The International Journal of Medical Science and Health Research, 2026)
Background: Virtual autopsy, or VA, is a non-invasive method that supports traditional autopsy (CA) by utilizing cutting-edge technologies including computed tomography, magnetic resonance imaging, and X-rays. In cases of pathological post-mortems (PMs) where cultural or religious restrictions limit the use of CA, VA can be employed. Comprehending the correlation between diagnostic quality and the precision of postmortem magnetic resonance imaging as a substitute for traditional autopsy might be advantageous in formulating strategies and mitigating the difficulty of precisely determining the cause of death in certain cases. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. Several websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: Based on credible sources such as Science Direct, SagePub, and PubMed, the analysis looked at more than 1,500 articles. After it was decided that eight publications needed to be looked at further, the entire article was examined in greater detail. Conclusion: PMMR is a high-sensitivity diagnostic tool that provides detailed information about structural abnormalities and fetal disease processes. It is crucial for neuroradiological examination in perinatal post-mortem settings and demonstrates high diagnostic accuracy. Combining PMCT and PMMR has demonstrated high sensitivity in identifying skeletal injuries and cardiomyopathies, but requires specialized training to minimize over-interpretation of non-specific findings.